1988
DOI: 10.2527/jas1988.661213x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Feeding Value of Supplemental Fat in Finishing Diets for Feedlot Steers Supplemented with and Without Monensin

Abstract: Two comparative slaughter trials and a metabolism trial were conducted. Treatments consisted of: 1) 0 fat, 0 monensin; 2) 4% yellow grease, 0 monensin; 3) 0 fat, 33 mg/kg monensin and 4) 4% yellow grease, 33 mg/kg monensin. Trial 1 involved 104 crossbred beef steers (267 kg) in a 140-d comparative slaughter trial. There were no interactions (P greater than .20) between supplemental fat and monensin on steer performance. Monensin supplementation decreased rate of weight gain (P less than .10) and feed intake (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
71
1
9

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 0 publications
17
71
1
9
Order By: Relevance
“…Zinn et al (2002) summarized available literature and suggested that post-ruminal starch digestion appears to be limited by accessibility of the amylolytic enzymes and not limitations in the amount of enzymes. It is Karr et al (1966), Hibberd et al (1985), Axe et al (1987), Zinn (1988Zinn ( , 1989Zinn ( , 1990Zinn ( , 1991, Streeter et al (1989Streeter et al ( , 1990Streeter et al ( , 1991, Hill et al (1991), Palmquist et al (1993), Streeter and Mathis (1995), Swingle et al (1999), Theurer et al (1999), Garcia et al (2000).…”
Section: Optimizing Site Of Digestion Advantagesmentioning
confidence: 99%
“…Zinn et al (2002) summarized available literature and suggested that post-ruminal starch digestion appears to be limited by accessibility of the amylolytic enzymes and not limitations in the amount of enzymes. It is Karr et al (1966), Hibberd et al (1985), Axe et al (1987), Zinn (1988Zinn ( , 1989Zinn ( , 1990Zinn ( , 1991, Streeter et al (1989Streeter et al ( , 1990Streeter et al ( , 1991, Hill et al (1991), Palmquist et al (1993), Streeter and Mathis (1995), Swingle et al (1999), Theurer et al (1999), Garcia et al (2000).…”
Section: Optimizing Site Of Digestion Advantagesmentioning
confidence: 99%
“…Samples were subjected to all or part of the following analysis: DM, ash, Kjeldahl N, ammonia N (AOAC, 2003); purines (Zinn and Owens, 1986); VFA concentrations of ruminal fluid (gas chromatography; Zinn, 1988); selenium and magnesium (atomic absorption spectrophotometry); chromic oxide (Hill and Anderson, 1958); NDF (Weizhong and Uden, 1998) and starch (Zinn, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…A associação de óleo e monensina diminuiu a concentração de acetato em relação ao óleo, mas não deferiu da monensina, sugerindo que a população microbiana sensível à monensina não é a mesma que aquela sensível ao óleo de soja, ou também, que a microbiota ruminal apresenta diferentes graus de sensibilidade em relação ao ionóforo ou ao óleo de soja. Resultados semelhantes foram observados por Zinn (1988), utilizando graxa amarela e monensina.…”
Section: Discussionunclassified
“…A proporção entre os AGV também foi alterada, com redução de acetato e elevação de propionato, no entanto, sem apresentar interação entre os tratamentos. Zinn (1988) não constatou interação entre graxa amarela (resíduo de gordura de restaurantes) e monensina sobre o desempenho animal, mas os produtos finais da fermentação ruminal foram alterados. Cant et al (1997) registraram efeito sinérgico entre monensina e óleo de peixe ao reduzir o consumo por vacas lactantes.…”
Section: Introductionunclassified